Staying in the Game: The 10‐Step Approach to Sustaining Geriatrics Education in Hospitalists and Subspecialty Providers. Issue 8 (15th July 2014) - Gillespie, Suzanne M.; Brandt, Lynsey E.; Chang, Anna; Chao, Serena H.; Corcoran, Amy M.; Miller, Rachel; Harper, G. Michael; Levine, Sharon A.; Medina‐Walpole, Annette
<x xml:space="preserve">Abstract</x> Geriatrics as a field has been fortunate to have the support of several philanthropic organizations to advance geriatrics education and training in the past two decades. Awardees of such grants were presented with unparalleled opportunities to develop new and innovative educational initiatives affecting learners at multiple levels and in multiple disciplines and specialties. The lessons learned from the Donald W. Reynolds Foundation initiatives about effect and sustainability are invaluable to the ongoing strategic development of geriatrics nationally. This article highlights successful educational initiatives developed at four institutions with past and current Donald W. Reynolds Foundation funding. Following an ice hockey playbook, this article identifies 10 strategies and initiatives to "stay in the geriatrics game" by training hospitalists and subspecialty providers. The authors' collective experience suggests that geriatrics educational initiatives can not only influence provider education, but also improve the care of older adults in multiple settings.